The direct and indirect effects of internal enablers on internal integration and business performance - Ruzo-Sanmartín, Emilio; Abousamra, Alaa A.; Otero-Neira, Carmen; Svensson, Göran (Journal of Business Economics and Management, 2023)
The present paper aims to assess both the direct as well as the indirect effects of internal enablers on internal integration and business performance in the supply chain. A full managerial comprehension of the connection between supply chain integration (SCI) and business performance is missing so far and earlier results are inconclusive. To fill this gap, this study expands the growing body of research on SCI and contributes to the SCM field by explaining the direct and indirect effects of internal enablers on internal integration and business performance. Results show that hierarchical organizational culture influences internal integration and supply chain performance, that top management support and information technology department size influence internal integration, and, finally, that supply chain performance impacts operational performance. These findings confirm the relevance for firms to pay attention to those key internal enablers of internal integration, and their benefits on business performance. Considering our results, future research should deepen on the influence of internal integration on business performance by focusing on the links between internal integration and the other dimensions of SCI, that is supplier and customer integration, as well as with the external side of the supply chain performance.